Prospective randomised comparison of arthroscopic versus mini-open rotator cuff repair of the supraspinatus tendon - Kasten, Philip; Keil, Christoph; Grieser, Thomas; Raiss, Patric; Streich, Nikolaus; Loew, Markus (International orthopaedics, 2011)
Purpose: The aim of the study was to evaluate whether arthroscopic (ASC) repair of rotator cuff ruptures causes less postoperative pain and better range of motion (ROM) in the early postoperative period than a mini-open (MO) technique. - Methods: Inclusion criteria were a rupture of the supraspinatus tendon with retraction with a maximum to the apex of the humeral head and minor fatty degeneration and atrophy of the muscle. Each group (n = 17) had similar demographics and preoperative magnetic resonance imaging (MRI) findings (mean age 60.1 years, SD 8.8, range 43–71). The ASC group underwent double-row repair with resorbable anchors; the MO group received a transosseous repair. The postoperative rehabilitation was standardised and equivalent in both groups. - Results: In the first week fewer nonsteroidal anti-inflammatory drug (NSAID) tablets were needed in the ASC group. Pain scores on the visual analogue scale were similar in the first three weeks; however, from week four to eight the MO group had less pain (p < 0.05). After six months, the Constant-Murley score and the ROM improved significantly (p < 0.05) in both groups without differences between the groups. Postoperative MRI revealed in three of 16 patients a discontinuity of the tendon in both groups; in the ASC group there were more patients (n = 9) with a thinning of the tendon compared to the MO group (n = 6). Conclusions: There was less use of NSAIDs in the first postoperative week in the ASC group, indirectly indicating less pain, but higher pain scores in the later course (weeks four to eight) compared to the MO group. ROM, MRI findings and the scores were similar after six months, demonstrating that both techniques are equivalent regarding the outcome in this period.
Gesehen am 21.07.2022